Fiat Corporation Conference Center: The Amalfi Coastline, Italy - Annette R. Haflich (Oz, 1984)
The beauty of the Amalfi coastline, and in particular the southern slope on the Tyrrenhenian Sea located between the Italian hilltowns of Sorrento and Positano, establishes the setting for the Fiat Corporation Conference center…